2013
DOI: 10.1039/c3cp51444g
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between polymorphism, pressure, spin-crossover and temperature in [Fe(PM-BiA)2(NCS)2]: a neutron powder diffraction investigation

Abstract: The pressure dependencies of the lattice parameters of the spin transition compound [Fe(PM-BiA)2(NCS)2] have been derived from neutron powder diffraction measurements at low temperature. The study of the compound [Fe(PM-BiA)2(NCS)2]-pI has first confirmed the atypical spin crossover behaviour under pressure of this compound that shows a pressure induced structural transition inducing the transformation into a different polymorph, [Fe(PM-BiA)2(NCS)2]-pII. This phenomenon avoids a first-order spin transition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 53 publications
4
19
0
Order By: Relevance
“…and Raman) of the molecule in its two spin states by molecular simulation (Figure 8). Particularly we found, in agreement with the experiment [30], that the Fe–N 6 octahedron is more distorted in the high-spin state than in the low-spin one, as illustrated by the distance changes: Δ d HS = 0.21 Å much larger than Δ d LS = 0.03 Å as well as for the angles extremes: Δθ HS = 26.4° > Δθ LS = 13.7°.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…and Raman) of the molecule in its two spin states by molecular simulation (Figure 8). Particularly we found, in agreement with the experiment [30], that the Fe–N 6 octahedron is more distorted in the high-spin state than in the low-spin one, as illustrated by the distance changes: Δ d HS = 0.21 Å much larger than Δ d LS = 0.03 Å as well as for the angles extremes: Δθ HS = 26.4° > Δθ LS = 13.7°.…”
Section: Resultssupporting
confidence: 91%
“…The latter is mainly explained by considerations on the crystal packing. More recently, preliminary experimental investigation of the (P, T) phase diagram by means of neutron diffraction have revealed that applying pressure to the orthorhombic polymorph induces a structural transition to the monoclinic polymorph [30] leading to an intricate spin and structural phases diagram. As it is further shown below, molecular simulation has been used to determine the full (P, T) phase diagram, overcoming the high experimental difficulty to obtain reliable high pressure crystal structure at variable (low) temperature as well as its high cost [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some compounds of the same series have shown a SCO at room temperature but for pressure higher than 700 MPa [46,47]. Let us recall that single crystals of [Fe(PM-PEA) 2 (NCS) 2 ] are well-known from variable temperature measurements [43] to crystallize in the monoclinic system in the HS state and in the orthorhombic system in the LS state; the unit-cell volume variation due to the thermal SCO being of the order of 3%.…”
Section: Sco At High-pressurementioning
confidence: 99%
“…21 The pressure-induced LS structure has only been reported in four of those studies, all concerning iron(II). 10,19 This is despite interest in probing the similarities and differences between the structures of the pressure-induced and temperature-induced LS states, 22 especially for metal ions which undergo anisotropic M-L changes (Jahn Teller), such as cobalt(II). Rather than full structure determinations, the effect of pressure is more commonly followed crystallographically by monitoring changes to the unit cell constants.…”
Section: Introductionmentioning
confidence: 99%